New observations and corrections concerning the trio of invasive hydromedusae Maeotias marginata (=M. inexpectata), Blackfordia virginica, and Moreisia sp. in the San Francisco Estuary - Mills, C.; Rees, J. T. (Scientia Marina, 2000)
New observations of Maeotias, Blackfordia, and Moerisia in low salinity waters of the San Francisco Bay estuary allow better understanding of the life cycles and natural history of these three genera of invading hydrozoans. Maeotias inexpectata Ostroumoff, 1896 is found to be a junior synonym of Maeotias marginata (Modeer, 1791). Moreover, M. inexspectata Ostroumoff, 1896b is an incorrect subsequent spelling of M. inexpectata Ostroumoff, 1896a. The clear presence of marginal statocysts in the medusa of this species places it back in the family Olindiidae of the Limnomedusae. Polyps previously attributed to Maeotias in San Francisco Bay are now known to belong to a Moerisia sp., whose medusa has also recently been found in the estuary system. Solitary Moerisia polyps have been found in the field amongst the general fouling fauna on floating docks in the Napa River. Small simple primary polyps of M. marginata were obtained in the laboratory. Polyps of Blackfordia virginica have been found in abundance in the field covering the valves of nonindigenous barnacles in the Napa River and laboratory-cultured colonies are pictured here along with their newly-released and juvenile medusae.Descripors: Blackfordia virginica, Maeotias marginata, Moerisia